Hidden symmetries of integrable conformal mechanical systems - Akopyan (Hakobyan) T. S. Tigran Stepanovich; Krivonos S. Sergey; Lechtenfeld O. Olaf; Nersessian A. P. Armen Petrosovich (2010, 2010)
Title screen